Assessing Farmers' Knowledge, Attitudes, And Behavioural Intentions in Relation to The Transfer of Alternative Wood Preservation Technologies in Rural Ethiopia - Gemechu Kaba; Omer Hinde; Azmera Belachaw; Asfaw Gelan (Journal of Techno-Social, 2024)
Alternative wood preservative technology prevents wood damage and enhances wood service life for local construction in contact with the ground contact. Hence, the promotion of wood preservative technology and the evaluation of knowledge, attitude, and behavioral intention necessitate a causal effect relationship assessment in rural Ethiopia. Farmers were invited for the training in rural kebele, where subterranean termites highly affected local construction with ground contact. During the training, theoretical, demonstration, and group discussion were used as methods for technology transfer. Accordingly, the causal effect relationship of knowledge, attitude, and behavioral intention was evaluated using PLS_SEM using Smart PLS 4 version software. The study results show that, due to local experience, using used motor oil is better preferred over others chemical preservatives. The practical method demonstration influences the attitude of farmers toward future applications. The causal effect analysis result shows that knowledge directly influences attitude (? = 0.609; P-value = 0.000), and subsequently, an attitude directly influences behavioral intention (? = 0.822; P-value = 0.000). Thus, attitude mediates the causal effect relationship between the knowledge and behavioral intention of the farmers. Therefore, the study implies that expanding knowledge of local experience and practical training on technical skills for rural farmers should be given primary attention for forest product technology promotion in rural areas.